WOMEN WHO CHOOSE NOT TO PARTICIPATE IN SURVEYS ON EATING DISORDERS - Beglin, S; Fairburn, C (1992)
Thirty-nine women chose not to participate in a survey on eating disorders. Their medical records revealed a high rate of eating problems. This finding, together with those of two related studies, suggests that such problems are overrepresented amongst those who elect not to take part in surveys of this type. As a result, estimates of the prevalence of eating disorders are likely to be underestimates: indeed, it may never be possible to get accurate figures for the prevalence of eating disorders.